Our Mutual Friend - Dickens, Charles, 1812-1870.; Gill, Stephen (London ; New York : Penguin Books, 1971)
John Harmon returns to England as his father's heir. Believed drowned under suspicious circumstances--a situation convenient to his wish for anonymity--John evaluates Bella Wilfer whom he must marry to secure his inheritance. The story is filled with colorful Victorian characters and incidents -- the faded aristocrats and parvenus gathered at the Veneering's dinner table, Betty Higden and her terror of the workhouse and the greedy plottings of Silas Wegg.
Keywords: Inheritance and succession -- Fiction; Social classes -- Fiction; Poor families -- Fiction; Deception -- Fiction; London (England) -- Fiction; London (England) -- Social life and customs -- 19th century -- Fiction; Satire; Historical fiction; Love stories